Spongillaflies (Neuroptera, Sisyridae) in Baltic amber - Wichard, Wilfried; Wedmann, Sonja; Weiterschan, Thomas (Zootaxa, 2016)
Two spongillaflies species are described and illustrated from Eocene Baltic amber: Paleosisyra minor n. sp. and Paleosisyra electrobaltica Wichard et al., 2009; the latter species was described based on a female and is now re-described in consideration of the male genitalia of two new male specimens. Extant Sisyridae comprise few species, and their fossil record is very scarce.